2020
DOI: 10.1007/s15010-020-01561-x
|View full text |Cite
|
Sign up to set email alerts
|

A challenging complication following SARS-CoV-2 infection: a case of pulmonary mucormycosis

Abstract: Severe acute respiratory syndrome coronavirus 2 infection might induce a significant and sustained lymphopenia, increasing the risk of developing opportunistic infections. Mucormycosis is a rare but severe invasive fungal infection, mainly described in immunocompromised patients. The first case of a patient diagnosed with coronavirus disease (COVID-19) who developed a pulmonary mucormycosis with extensive cavitary lesions is here reported. This case highlights how this new coronavirus might impair the immune r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
138
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(147 citation statements)
references
References 20 publications
2
138
0
7
Order By: Relevance
“…In a case described of severe COVID-19 associated with fungal coinfection, cell counts revealed that there was a progressive increase in white blood cell count and neutrophils while lymphocytes progressively decreased. 9 It is hypothesised that SARS-CoV-2 infection may affect CD4+ and CD8+ T-cells, which are highly involved in the pathological process of COVID-19 infection. It has been shown that in severe COVID-19 cases, there is a reduction in the absolute number of lymphocytes and T-cells, which is associated with the worst outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In a case described of severe COVID-19 associated with fungal coinfection, cell counts revealed that there was a progressive increase in white blood cell count and neutrophils while lymphocytes progressively decreased. 9 It is hypothesised that SARS-CoV-2 infection may affect CD4+ and CD8+ T-cells, which are highly involved in the pathological process of COVID-19 infection. It has been shown that in severe COVID-19 cases, there is a reduction in the absolute number of lymphocytes and T-cells, which is associated with the worst outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…All six previously reported patients with COVID-associated mucormycosis had received broad-spectrum antibacterial medications initially and were tested for non-bacterial etiologies only after their clinical status worsened. Two of these patients with pulmonary mucormycosis received IV corticosteroids and a single dose of tocilizumab [11,12]. That all three patients with pulmonary disease, including the one presented here, died, underscores the severity of mucormycosis in the setting of severe COVID-19.…”
Section: Discussionmentioning
confidence: 57%
“…The case presented here is thus one of the first reported cases of COVID-associated mucormycosis and is notable for the presence of necrotizing pneumonia and empyema. The two pulmonary COVID-associated mucormycosis cases published previously involved a 49-year-old man in Yuma, Arizona, who developed bronchopleural fistula requiring thoracotomy and fistula repair with pleurodesis and a 66-year-old man in Sassari, Italy, with pulmonary mucormycosis with extensive cavitary lesions, who was managed medically with LAmB given his high operative risk [11,12]. Neither patient had an underlying condition before COVID-19, and both died during the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less common sites included pulmonary mucormycosis (5/68), and 1case each of cutaneous, gastrointestinal tract and fulminant mucormycosis. India accounted for 75% of published cases (51/68) (2-10), followed by United States of America (9/68) (11)(12)(13)(14)(15)(16)(17)(18), Iran (4/68) (19-21) and 1 case each from Brazil (22), Mexico (23), Italy (24) and Austria (25). Most patients suffering this complication of mucormycosis had some underlying co-morbidity mainly diabetes mellitus, but infections in immunocompetent persons have also been seen.…”
Section: To the Editormentioning
confidence: 99%